2013
DOI: 10.1007/s10654-013-9829-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum uric acid and the metabolic syndrome among a middle- and old-age Chinese population

Abstract: Our aim was to study whether there is causal association between serum uric acid and metabolic syndrome (MetS). A cross-sectional study was performed, including a total of 27,009 subjects (23,345 subjects having uric acid data) from the Dongfeng-Tongji Cohort study. The MetS was defined by the International Diabetes Foundation criteria of 2005. Association analysis was performed by logistic regression. A genetic risk score was calculated by adding the uric acid increasing alleles in two SNPs (rs11722228 in SLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 34 publications
5
47
1
Order By: Relevance
“…Several cross-sectional and longitudinal studies substantially confirm our results, finding an association between UA and worse metabolic profile stronger in women than in men (37)(38)(39)(40)(41)(42)(43)(44). This different association between genders seems to be attributable to several factors, but particularly to the deficiency of estrogens that have uricosuric and metabolic effects (14).…”
Section: Discussionsupporting
confidence: 83%
“…Several cross-sectional and longitudinal studies substantially confirm our results, finding an association between UA and worse metabolic profile stronger in women than in men (37)(38)(39)(40)(41)(42)(43)(44). This different association between genders seems to be attributable to several factors, but particularly to the deficiency of estrogens that have uricosuric and metabolic effects (14).…”
Section: Discussionsupporting
confidence: 83%
“…In line with previous studies [21][22][23] we reported higher serum uric acid level in women with MetS, comparing to those without MetS. Moreover, in a prospective study conducted by Zurlo et al [24] high serum uric acid levels significantly and independently predicted MetS in older women, but not in men, over a 4.4-year follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…Epidemiological and clinical evidence supports the strong link between serum uric acid (SUA) and obesity in different populations. For example, Dai et al 3. performed a cross-sectional study, including 27 009 middle- and old-age Chinese subjects, observed that BMI significantly increased with increasing SUA quintiles.…”
mentioning
confidence: 99%